Alveolar ridge preservation?: Decision making for dental implant placement. ¿Preservación del reborde alveolar? Toma de decisión ante la colocación de implantes dentales - Ford Martinell, Vanessa Louise; Hanly, Gianna; Valenzuela, Juliana; Herrera Orozco, Lina Marcela; Muñoz Zapata, Sebastián (CES Odontología, 2013)
Bone resorption is a physiological consequence of tooth loss that could be a significant functional andan esthetic risk for dental implants. The dimensional changes of the alveolar ridge could be managedwith different graft materials and surgical techniques that have been reported in the scientific literature.The purpose of this review is to explore the indications and present actual techniques to help preventresidual ridge resorption, as much as possible, guaranteeing the success of Prosthodontic rehabilitationwith implants.Key words:Alveolar ridge preservation, Alveolar ridge resorption, Tooth extraction, Bone grafting, Dental implants. La reabsorción ósea es una consecuencia fisiológica de la pérdida dental que puede convertirse en un riesgofuncional y estético significativo para la colocación de implantes dentales. Los cambios dimensionales delreborde alveolar pueden ser manejados con diferentes materiales de injerto y procedimientos quirúrgicosreportados en la literatura. El propósito de esta revisión es presentar las indicaciones y técnicas actualesutilizadas para ayudar a prevenir, en lo posible, la reabsorción del reborde residual asegurando el éxitode la rehabilitación sobre implantes.Palabras clave:Preservación del reborde alveolar, Reabsorción ósea, Extracción dental, Injerto óseo, Implantes dentales.